Fixed topology Thévenin equivalent fully detailed model for nonlinear capacitances. Issue 1 (1st January 2017) - Zhang, Feng; Wang, Kangping; Yang, Xu; Cheng, Shi
Abstract : A datasheet‐based fully detailed model for nonlinear capacitances is proposed to significantly reduce the simulation time on the turn‐on and turn‐off transitions of power electronic circuits. In this model, a nonlinear capacitance is Thévenin equivalent to a voltage source in series with a constant resistance, and the nonlinear part is represented in the voltage source. So, unchangeable admittance matrix is achieved regarding the nonlinear part of capacitances as excitations. Appreciable calculation speedup is gained while good accuracy is maintained.